1998
DOI: 10.1063/1.120599
|View full text |Cite
|
Sign up to set email alerts
|

n -type delta-doped strained quantum well lasers for improved temperature-dependent performance

Abstract: It is demonstrated that the incorporation of Te n-type δ doping close to a single-strained InGaAs/GaAs quantum well improves the temperature stability of the laser, as indicated by the higher characteristic temperature and by the reduced sensitivity of the threshold current to temperature variations. This improvement results from the strong coupling between the quantum well and the δ-doping well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The positive ion background will reduce the population of thermal diffusive electrons in the SCH and as a result will improve the T 0 laser parameter as already measured for quantum-well lasers. 5 Our physical explanation allows one to tune the resonance-emitted wavelength by increasing the doping concentration. A deeper confinement of the ␦-doping ground state allows scattering processes which result in capture by larger dots.…”
Section: Discussionmentioning
confidence: 95%
“…The positive ion background will reduce the population of thermal diffusive electrons in the SCH and as a result will improve the T 0 laser parameter as already measured for quantum-well lasers. 5 Our physical explanation allows one to tune the resonance-emitted wavelength by increasing the doping concentration. A deeper confinement of the ␦-doping ground state allows scattering processes which result in capture by larger dots.…”
Section: Discussionmentioning
confidence: 95%
“…These heterostructures were fabricated into devices with good performance [9]. Te doping has also been used in metal-organic chemical vapor deposition to dope InGaAs/AlGaAs HEMTs [10] as well as quantum well lasers [11]. An additional motivation for studying Te doping in InP HEMTs is the Si deactivation problem.…”
Section: Introductionmentioning
confidence: 99%
“…In III-V compound semiconductors such as GaAs, FETs with characteristics superior to those of conventionally doped transistors have been fabricated using the delta-doping technique [6], which can achieve very narrow doping distribution along the epitaxial growth direction and up to now has been studied in a variety of materials and devices [7][8][9]. It was recently demonstrated that the inclusion of delta doping could improve laser stability in the face of temperature variations, in comparison with conventional quantum well lasers [10].…”
Section: Introductionmentioning
confidence: 99%